Learning Strategies at SD Muhammadiyah 5 Porong during the Covid 19 Pandemic - Muhammad Naufal Yudha Pratama (International Consortium of Education and Culture Research Studies, 2021)
This study aims to determine how Muhammadiyah 5 Porong Elementary School applies learning strategies during the Covid19 pandemic. This research was conducted by means of descriptive methods and interviews with one of the teachers at the school. This is an observation of teaching and learning activities at SD Muhammadiyah 5 Porong during the covid pandemic. Apparently, the school uses online methods and is doing well in learning. To interact with students, educators usually use video calls in teaching activities. Educators also do several ways to improve student learning.